Numerical study on contact zone in an interfacial crack - Shen, Hongnian. (2008)
This thesis presents an analysis for contact zone near an interfacial crack tip by using the commercial FEM software ANSYS 5.0 and 5.3. The numerical study with various parameters extended from elastic to elastic-plastic range. In the elastic range, the study shows that the contact zone occurs when shear loading is dominant along certain directions. The maximum contact zone size occurs when the specimen is subjected to pure shear loading. Material constant mismatch, such as Young's modulus ratio, plays a part in the size of the contact zone. Furthermore, the effect of friction between crack surfaces on fracture parameters is also studied for some cases. For elastic-plastic materials, the ductile solid is assumed to obey the J2 flow theory of plasticity under plane strain conditions. The results show the plastic deformations generally reduce the size of contact zone near the crack tip, and have a big influence on fracture parameters. In addition, plastic zone shapes are compared with different loading and material combinations.